Pengembangan Buku Panduan Program Mentoring Keagamaan Islam dalam Pembinaan Akhlak Siswa di SMA Negeri 1 Simangambat - Frimayanti Siagian; Muhammad Darwis Dasopang; Fauziah Nasution (Lentera Ilmu: Jurnal Kependidikan, Riset dan Teoritis, 2025)
The success of character education in schools depends greatly on teachers as mentors and role models. However, at SMA Negeri 1 Simangambat, issues like lack of discipline and disrespect still occur. To address this, the study developed an Islamic religious mentoring program aimed at improving students’ moral character. Using a Research and Development (R&D) method based on Plomp’s model, the research involved identifying problems, designing, implementing, and evaluating a mentorship guidebook. Results showed the product is highly valid (92.63%), practical (88.17%), and effective, with an N-Gain score of 0.48 and significant improvement (t = 1.70; p = 0.00). Thus, the guidebook is appropriate for use in fostering Islamic character education at SMA Negeri 1 Simangambat.